Students’ Perceptions and Attitudes Toward Google Classroom in English Reading - Mardiatun Nissa; Daffa Nirwana Wahyudi; Siti Aulia Sintia; Naf’an Tarihoran (LPPM Universitas Islam Darul `Ulum Lamongan, 2026)
This research was inspired by the advancements in technology within the education sector that have led to the adoption of online learning platforms, like Google Classroom, for teaching the English language. The purpose of the study is to investigate students’ views, feelings, and difficulties in using Google Classroom for English reading instruction. A quantitative descriptive methodology is used, relying on a survey approach. Data were gathered through an online questionnaire distributed to students who had experience with Google Classroom. The findings suggest that students have favorable views and attitudes towards Google Classroom, especially in terms of the accessibility of materials, enhanced reading comprehension, and a sense of comfort during the learning experience. However, several challenges were identified, including internet connectivity issues, data plan costs, and limited internet speeds. These findings indicate that Google Classroom is an effective learning platform for supporting English reading instruction, though technical obstacles remain to be addressed. Therefore, the use of Google Classroom needs to be optimized to account for the readiness of the technological infrastructure, enabling the learning process to run more effectively.